Modification of twin crystal Cd0.5Zn0.5S photocatalyst with up-conversion nanoparticles for efficient photocatalytic H2-production. (20th September 2019) - Zhao, Haitao; Liu, Heyuan; Guo, Luyan; Xing, Chuanwang; Li, Xiyou
Abstract: The photocatalytic H2 -production by solar light has been considered a promising technology to converse solar energy into carbon-free hydrogen. The development of efficient and stable catalysts is the most urgent problem in this technology. Up to now, twin crystal Cd0.5 Zn0.5 S solid solution has been regarded as the best efficient pristine sulphide catalysts for visible-light-driven hydrogen production. Its catalytic activity can be remarkably improved further by loading suitable co-catalyst, such as PdP~0.33 S~1.67, noble metal Pt, and NiSx . However, these twin crystal Cd0.5 Zn0.5 S-based nanocomposites can only response to partial (wavelength less than 520 nm) visible light irradiation. Large amount of visible light and near infrared light (NIR) in solar spectrum can not be absorbed by Cd0.5 Zn0.5 S and, therefore, do not contribute to the H2 production. In this work, β-NaYF4 :Yb 3+, Tm 3+, Er 3+ up-conversion nanoparticles (UPNs) are prepared by a hydrothermal process and the corresponding nanocomposite photocatalyst (twin crystal Cd0.5 Zn0.5 S/β-NaYF4 :Yb 3+, Tm 3+, Er 3+ (T-CZS/UPNs)) based on this kind of up-conversion nanoparticles and twin crystal Cd0.5 Zn0.5 S nanocrystal is successfully prepared for the first time. The compositions, morphologies, and optical properties of the T-CZS/UPNs are investigated using XRD, SEM, HRTEM, UV–vis–NIR absorption spectra and photoluminescence (PL) spectrum. The photocatalytic hydrogen evolution experiments are performed under the irradiation of visible light, NIR light or simulated solar light, respectively. The H2 production rate over T-CZS/UPNs-15 nanocomposite under the irradiation of simulated solar light in the presence of Na2 S/Na2 SO3 as sacrificial agent is measured to be 159.3 mmol/h/g, which is 3.4 times higher than that of pristine T-CZS nanocrystals. In particular, this nanocomposite exhibits also significant photocatalytic hydrogen production rate (0.497 mmol/g/h) under NIR light irradiation ( λ  > 800 nm), reveals the contribution of NIR light to H2 production via an photon-up-conversion process. This work gives an innovative vision in constructing efficient photocatalysts to make the efficient use of NIR solar light. Graphical abstract: A photocatalyst composed of β-NaYF4 :Yb 3+, Tm 3+, Er 3+ up-conversion nanoparticles (UPNs) and twinned Cd0.5 Zn0.5 S nanocrystal (T-CZS/UPNs) is successfully synthesized by a facile two-step hydrothermal method. Compared with pristine T-CZS, the T-CZS/UPNs nanocomposite shows superior photo-catalytic hydrogen production activity under NIR light irradiation as well as simulated solar light.Image 1 Highlights: UPNs nanoparticle modified twin crystal Cd0.5 Zn0.5 S photocatalyst is prepared. The photocatalytic activity of twin crystal Cd0.5 Zn0.5 S is significantly improved. The new photocatalyst show better NIR-light response. The mechanism for photocatalytic activity improvement is investigated.